Konseling Berbasis Kerafian Lokal Indonesia sebagai Upaya Penguatan Karakter Kebangsaan - Edris Zamroni (Jurnal Bimbingan dan Konseling Terapan, 2019)
At 2045 Indonesia will have a bonus demography of human resources that will contribute greatly in the progress of NKRI. Is a big challenge for all parties, especially since starting January 2016 also enacted ASEAN Economic Community (ASEAN Economic Community) that allows the entry of various cultures from the ASEAN community. Needed human resources characterized so that along with the progress of civilization, the community retains its cultural character. The formation of karatker should start from education from an early age. Counseling and Counseling as an integral part of education has an important role in shaping the character of learners. For that it is necessary various strategies of guidance and counseling services, especially counseling specifically characterized the Indonesia-an taken from local wisdom and cultural values of Indonesia. Some examples of local wisdom that can be raised as the basic values of counseling are religious-spiritual values, kejawen values, sunda values, tri hita karana (bali), and are generally represented by the Indonesian education motto Ing Ngarso sung Tulodho, Ing Madyo Mangun Karso, Tut Wuri Handayani. The core value infusion of the philosophy of each local wisdom must be done so that the national character of Indonesia still exist in the midst of globalization and the progress of civilization. The main values of each culture will provide alternative references to problem solving, alteration and strengthening behavior that affirm the national identity of Indonesian society.